Alterations in the intestinal fungal microbiome of patients with severe fever with thrombocytopenia syndrome - Meng-Yu Liu; Sheng-Fu He; Yu-Yao Li; Jiao-Jiao Shen; Jia-Jia Li; Ya-Sheng Li; Yan-Yan Liu; Ting Wu; Jia-Bin Li; Li-Fen Hu (Journal of Infection and Public Health, 2025)
Background: Aspergillus coinfection in patients with severe fever with thrombocytopenia syndrome (SFTS), is a serious clinical challenge associated with increased mortality. Understanding the factors contributing to this co-infection is crucial for improving patient outcomes. This study aimed to reveal the role of the intestinal mycobiome in SFTS severity and the risk of Aspergillus coinfection, with the goal of identifying potential therapeutic targets. Methods: Fecal samples were collected from 80 patients both during their hospitalization and post-discharge. Internal transcribed spacer (ITS) amplicon sequencing and fungal profiling of intestine were performed. R statistical software (version 3.5.1) was used for data processing and analysis. Results: The intestinal mycobiomes of SFTS patients showed strong alterations characterized by increased Aspergillus species, and a highly heterogeneous mycobiome conﬁguration compared to healthy controls. The Aspergillus had a positive correlation with coinfection of invasive pulmonary aspergillosis (IPA) and disease severity of SFTS (p < 0.001), whereas Saccharomycetales and Candida were more abundant in SFTS patients without IPA (p < 0.001). In SFTS patients with IPA, A. subversicolor, A. flavus and A. penicillioides were the three most common fungal species. Longitudinal dynamic detection revealed that patients who experienced significant fluctuations in their intestinal mycobiome tended to have more severe illness. After recovering, the gut mycobiome of patients can recover and stabilize within a month. Conclusion: The research highlighted enrichment of intestinal Aspergillus was conducive to IPA and disease severity in SFTS patients. Monitoring the gut mycobiome could potentially be used as a biomarker to assess disease severity of SFTS.